2015
DOI: 10.3945/ajcn.114.084889
|View full text |Cite
|
Sign up to set email alerts
|

Effects of animal source food and micronutrient fortification in complementary food products on body composition, iron status, and linear growth: a randomized trial in Cambodia

Abstract: No difference was found between the locally produced products (WF and WF-L) and the CSBs. Micronutrient fortification may be necessary, and small fish may be an affordable alternative to milk to improve complementary foods. The dietary role of edible spiders needs to be further explored. This trial was registered at controlled-trials.com as ISRCTN19918531.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
100
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(106 citation statements)
references
References 33 publications
3
100
1
2
Order By: Relevance
“…These foods were dubbed “WinFoods.” The WinFood project was carried out in parallel in Kenya and Cambodia from 2009 to 2012. In each site, processed complementary food products were formulated and produced on the basis of locally available foods and optimized for nutrient composition with emphasis on iron and zinc (Kinyuru et al, ; Kinyuru et al, ; Skau et al, ). Prior to the final decision on formulations, the acceptability of the products was assessed among mothers and infants (Konyole et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These foods were dubbed “WinFoods.” The WinFood project was carried out in parallel in Kenya and Cambodia from 2009 to 2012. In each site, processed complementary food products were formulated and produced on the basis of locally available foods and optimized for nutrient composition with emphasis on iron and zinc (Kinyuru et al, ; Kinyuru et al, ; Skau et al, ). Prior to the final decision on formulations, the acceptability of the products was assessed among mothers and infants (Konyole et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that micronutrient fortification may be necessary, and small fish may be an affordable alternative to milk to improve complementary foods. The Cambodian trial also showed that, despite the daily complementary food supplement, the children became increasingly stunted over the intervention period (Skau et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In Cambodia, micronutrient fortification in rice-based complementary food products was studied using animal sourced food such as the local fish and tarantula spider Haplopelma sp. (Araneae: Theraphosidae) (86) . The latter is eaten in Cambodia and traded in local food markets.…”
Section: Micronutrientsmentioning
confidence: 99%
“…Limitations to utilising animal protein isolates like whey protein concentrate (WPC) include: they are costly, may not provide the protein quantity to support linear growth in suggested amounts, and may lack beneficial bioactive components reported as important components of supporting growth ( 18 ) . A recent field trial comparing CSB+ against a complementary food product containing an animal-source protein found no difference in Fe status, or lean mass between protein-rich complementary foods in children at 6 months of age for 9 months, although there were significant improvements in knee–heel height ( 19 ) . Utilisation of soya-based proteins may be a safe, cost-effective and efficacious alternative to WPC ( 20 ) , and therefore, whey and soya protein may similarly enhance protein quality of FBF by providing amino acids that are highly bioavailable.…”
mentioning
confidence: 99%